Predicting changes in student engagement in university physical education: Application of control-value theory of achievement emotions. (March 2017) - Garn, Alex C.; Simonton, Kelly; Dasingert, Timothy; Simonton, Angela
Abstract: Objectives: Based on Pekrun's (2006) control value theory of achievement emotions, this study examined both distal and proximal predictors of change in students' behavioral and emotional engagement during one semester of university physical education classes. Design: Short-term longitudinal design. Method: Students ( N  = 202) completed questionnaires on three separate occasions during one semester. At the beginning of the semester, demographic information and behavioral and emotional engagement were reported. At the mid-point in the semester, control beliefs, extrinsic value beliefs, and discrete activity emotions toward the physical education context (i.e., enjoyment; anger; boredom) were completed. At the end of the semester, behavioral and emotional engagement were measured once again. Results: A series of confirmatory factor analyses provided evidence for factor validity and reliability in the measured constructs and longitudinal measurement invariance tests established that any detected change in student engagement was associated with true change. Findings from a path analysis revealed that initial emotional engagement was a predictor of control and extrinsic value appraisals as well as enjoyment and boredom, but not anger. Extrinsic value positively predicted enjoyment while control negatively predicted anger. Finally, a distinct pattern of relations was established between enjoyment, boredom, and changes in engagement. Conclusions: Differences in the predictive relations of boredom and anger on changes in student engagement highlights the unique contributions of measuring discrete emotions. Overall, findings partially support the applicability of using Pekrun's control value framework in physical activity settings. Highlights: A theoretical model of control-value theory of achievement emotion was tested. Enjoyment positively predicted changes in behavioral and emotional engagement. Boredom negatively predicted changes in behavioral and emotional engagement. Anger was not a predictor of changes in behavioral and emotional engagement.